Public Relation Management to Improve Open And Distance Higher Education Images Through Social Media - Mega Suteki; Sumartono Sumartono; Tjahjanulin Domai (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This study attempts to explain the management of public relations and the inhibiting factors in improving the image of open and distance higher education through social media at the Open University.Â The method used is a qualitative method. The Findings indicate that planning community relations activities in the Open University Surabaya based on guidelines at the Central Open University. Organizing public relations activities in Open University Surabaya includes setting up staff members in managing social media account anf websites; regulating the staff structure and delegating work; communication done both internally and externally; program implementation divide into routine and incidental programs; supervision is carried out by coordinator and head of Open University Surabaya; the modification function is carried out through an evaluation meeting. It was found that internal barriers in the form of mastering diverse student background, information technology understanding, and heavy staff workloads while the external obstacle is internet network infrastructure.